Reprogramming Macrophage Metabolism and its Effect on NLRP3 Inflammasome Activation in Sepsis - Luo, Ruiheng; Li, Xizhe; Wang, Dan (Frontiers in Molecular Biosciences, 2022)
Sepsis is a deadly multiorgan dysfunction syndrome and has no specific therapeutic strategy. Inflammasomes are a group of multi-protein signaling complexes which play vital roles in the development of sepsis. Among the subtypes of inflammasomes, the activation of NLRP3 inflammasome in macrophages was proven to be responsible for most. Recent studies have revealed that there is dramatic reprogramming of macrophage metabolism in sepsis, and this dysregulation has a closely relationship with the activation of NLRP3 inflammasome. With more and more evidence demonstrating the mechanism of metabolism reprogramming induced NLRP3 activation in macrophages, the key enzymes and metabolites participated in this regulation becomes gradually clear. In this review, we summarized the detail mechanism of the metabolic reprogramming process and its important role in the NLRP3 activation of macrophages in sepsis. This mechanism summarization will shed light on the applicational potential of metabolic regulatory molecules in the treatment of sepsis.